Extracellular vesicles mediate inflammasome signaling in the brain and heart of Alzheimer’s disease mice - Cyr, Brianna; Cabrera Ranaldi, Erika D. L. R. M.; Hadad, Roey; Dietrich, W. Dalton; Keane, Robert W.; de Rivero Vaccari, Juan Pablo (Frontiers in Molecular Neuroscience, 2024)
Introduction Alzheimer’s disease (AD) is an inflammatory neurodegenerative disease characterized by memory loss and cognitive impairment that worsens over time. AD is associated with many comorbidities, including cardiovascular disease that are associated with poorer outcomes. Comorbidities, especially heart disease and stroke, play a significant role in the demise of AD patients. Thus, it is important to understand how comorbidities are linked to AD. We have previously shown that extracellular vesicle (EV)-mediated inflammasome signaling plays an important role in the pathogenesis of brain injury and acute lung injury after traumatic brain injury. Methods We analyzed the cortical, hippocampal, ventricular, and atrial protein lysates from APP/PS1 mice and their respective controls for inflammasome signaling activation. Additionally, we analyzed serum-derived EV for size, concentration, and content of inflammasome proteins as well as the EV marker CD63. Finally, we performed conditioned media experiments of EV from AD patients and healthy age-matched controls delivered to cardiovascular cells in culture to assess EV-induced inflammation. Results We show a significant increase in Pyrin, NLRP1, caspase-1, and ASC in the brain cortex whereas caspase-8, ASC, and IL-1β were significantly elevated in the heart ventricles of AD mice when compared to controls. We did not find significant differences in the size or concentration of EV between groups, but there was a significant increase of caspase-1 and IL-1β in EV from AD mice compared to controls. In addition, conditioned media experiments of serum-derived EV from AD patients and age-matched controls delivered to cardiovascular cells in culture resulted in inflammasome activation, and significant increases in TNF-α and IL-2. Conclusion These results indicate that EV-mediated inflammasome signaling in the heart may play a role in the development of cardiovascular diseases in AD patients.